Using the information needs of internet users in combating disruptive innovation in the news paper industry - Conradie, D. P.; Diederichs, Pedro (Department of Communication Science, University of the Free State, 2012)
This article focuses on the relatively new concept of disruptive innovation, which has proved to be a useful analytical tool for understanding how technological innovation can play an important role in shaping many industries in society. The impact of disruptive innovations is perceived as a serious problem by most traditional newspapers, and even as threatening the future existence of the newspaper industry in its current form. Also relevant is the so-called Newspapernext strategy, a four-step strategy designed specifically for newspapers concerned about the impact of disruptive innovations. The first of the four steps to combat disruptive innovations consists of determining the information needs of a sample representing a potential new market for the newspaper. The study described in this article consists of an online survey of information needs, conducted amongst a randomly drawn sample of South African Internet users, and is an application of the first phase of the Newspapernext strategy. The article identifies and discusses patterns of information needs found among the respondents, and makes suggestions on how the findings can be implemented by newspapers wishing to proactively combat disruptive innovations.
Keywords: Disruptive innovation; Newspapers; Technology